Not an Odd-Bird, But an Augury. Yugoslav Youth Press in the Turmoil of 1960s and 1970s (KULT_online, 2018)
The book analyzes Yugoslav youth press in the 1960s and 1970s through the conceptual lens of alternative media, originating in Western media studies. Three Yugoslav peculiarities informed the development of this media genre: self-management doctrine, introduction of market elements into economy, and decentralization of the federation. By comparing the youth media outlets in the republican centers of Belgrade, Zagreb and Ljubljana, the author points out the crucial role of youth press in 1968 revolts, as well as the contextually induced ideological differences between the three mediascapes. The book also analyzes the blossoming of the punk scene and its social function during the 1970s, and important design-oriented innovations that this type of media introduced to the Yugoslav public. With its innovative methodology and diligently researched sources, this monograph represents a welcome addition to the burgeoning field of media studies dealing with the Cold War era.